Flutter analysis of cable stayed bridge. (2017) - Sukamta; Guntorojati, Ireng; Fariduzzaman
Abstract: Aerodynamic stability is one of the most important issues in wind resistance design for long-span bridges; various studies have been carried out on it. One of the most dangerous among various aeroelastic instabilities is flutter, which is the dynamic instability phenomenon wherein at some critical wind speed the bridge will oscillate and collapse. This paper discusses the flutter speed of the cable stayed bridge by means of numerical analysis as well as experimental. Numerical analysis of flutter speed was conducted based on the eight extracted aerodynamic derivatives. The Flutter Margin Method of Zimmerman was used to predict flutter speed of the experimental results. The analysis results showed that the critical flutter velocity based on the flutter derivatives was also confirmed by the experimental test results. It is concluded that the result from numerical analysis is close to that of the experimental test.